Guest inclusion in porous metal-organic crystals and high-pressure single-crystal X-ray diffraction analysis at low temperatures - Kutama, Aluwani (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.